Molecular Characterization and Phylogenetic Analysis of Fasciola gigantica Based on ITS-1 Genetic Marker and copro-epidemiological Survey from Ruminants of Pakistan - Mehmood, Naunain; Zulfiqar, Shafiah; Muqaddas, Hira; Hasnain, Muhammad; Zheng, Yadong; Bisetegn, Habtye [UNESP]; Ahmed, Fahad; Khan, Zafar Iqbal; Iqbal, Furhan (Springer Nature, 2024)
Purpose: Fascioliasis is a zoonotic parasitic disease spread by genus Fasciola that causes considerable health and economic losses to both humans and livestock. Pakistan is an endemic region for fascioliasis and only a few molecular studies have been conducted to describe the etiology of disease in the country. Methods: Current study involved the molecular characterization of adult fluke specimens (n = 31) through ITS-1 region of rDNA collected from four host species (sheep, goats, cattle and buffaloes) of district Sargodha. Moreover, coprology based epidemiology (n = 28620) and association of different risk factors with disease prevalence was also determined. Additionally, an overview of prevalence of fascioliasis in Pakistan, including molecular studies in the four provinces and livestock species, was also carried out. Results: The phylogenetic analysis revealed that Fasciola gigantica was the main etiological agent infecting the livestock species of this region. The coprological survey revealed an overall prevalence of 30.18% among the livestock species (sheep = 32.31%, goats = 30.67%, cattle = 31.01%, buffaloes = 25.23%). It was inferred that females were slightly more susceptible to infection (32.59%) and that the older age group had higher infection rate (34.01%) in all the host species. Conclusion: The current study suggests that fascioliasis is a disease of primary concern indicating its status as one of the prevalent diseases affecting livestock in this region. It was also concluded that both Fasciola gigantica and Fasciola hepatica existed among the infected animals in addition to presence of hybrid/intermediate form in Pakistan with F. gigantica as dominant species in Punjab province.
Keywords: Coprology; Epidemiology; Fasciola gigantica; ITS-1; Pakistan; Phylogeny